Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijms22010360
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Islets Accumulate Cadmium in a Rodent Model of Cadmium-Induced Hyperglycemia

Abstract: Cadmium (Cd) is an anthropogenic as well as a naturally occurring toxicant associated with prediabetes and T2DM in humans and experimental models of Cd exposure. However, relatively few studies have examined the mechanism(s) of Cd-induced hyperglycemia. The purpose of this study was to examine the role of pancreatic islets in Cd-induced hyperglycemia. Male Sprague–Dawley rats were given daily subcutaneous doses of Cd at 0.6 mg/kg over 12 weeks. There was a resulting time-dependent increase in fasting blood glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Thus, Cd-induced nephropathy may contribute, in part, to an elevation of plasma glucose levels among the subjects in the present study, which accentuates the central role of kidneys in the maintenance of plasma glucose levels [ 52 , 53 ]. These notions are in line with experimental studies in rats, where daily subcutaneous doses of Cd at 0.6 mg/kg for 12 weeks caused proteinuria [ 54 ], and hyperglycemia [ 55 ]. Half of the subjects in the present study were diagnosed with type 2 diabetes ( Table 2 ), and those with Cd and Pb exposure profiles 2 and 3 faced a 3–4.2-fold increment in the likelihood of having a diabetes diagnosis ( p = 0.002−0.009), while subjects with low eGFR were 2.9-times more likely to be diagnosed with diabetes.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, Cd-induced nephropathy may contribute, in part, to an elevation of plasma glucose levels among the subjects in the present study, which accentuates the central role of kidneys in the maintenance of plasma glucose levels [ 52 , 53 ]. These notions are in line with experimental studies in rats, where daily subcutaneous doses of Cd at 0.6 mg/kg for 12 weeks caused proteinuria [ 54 ], and hyperglycemia [ 55 ]. Half of the subjects in the present study were diagnosed with type 2 diabetes ( Table 2 ), and those with Cd and Pb exposure profiles 2 and 3 faced a 3–4.2-fold increment in the likelihood of having a diabetes diagnosis ( p = 0.002−0.009), while subjects with low eGFR were 2.9-times more likely to be diagnosed with diabetes.…”
Section: Discussionsupporting
confidence: 80%
“…Prior research in animal models identi ed a dysregulation of glucose metabolism, speci cally, a relationship between Cd exposure and increased blood glucose levels [5,6]. As reported, Cd exposure induced hyperglycemia, altered oxidative status and led to pancreatic β-cell dysfunction [7][8][9][10]. Our research group also found that Cd decreased serum insulin concentrations and induced insulin resistance [11].…”
Section: Introductionsupporting
confidence: 61%
“…However, it should be noted that not all studies have found significant associations between markers of Cd exposure and diabetes mellitus [ 8 ]. Numerous short-term and long-term in vivo Cd exposure models have shown Cd to cause hyperglycemia and disrupt glucose homeostasis in experimental animals [ 9 , 10 , 11 ]. The exact mechanism of action of the Cd-induced disruption of glucose homeostasis is unknown.…”
Section: Introductionmentioning
confidence: 99%